2008
DOI: 10.1088/0034-4885/71/4/044501
|View full text |Cite
|
Sign up to set email alerts
|

Scanning probe microscopy of oxide surfaces: atomic structure and properties

Abstract: The intersection of two fields, oxide surface science and scanning probe microscopy (SPM), has yielded considerable insight on atomic processes at surfaces. Oxide surfaces, especially those containing transition metals, offer a rich variety of structures and localized physical phenomena that are exploited in a wide range of applications. Nonlinear optics, superconductivity, ferroelectricity and chemical catalytic activity are but a few. Furthermore, the challenges and solutions associated with the chemistry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 156 publications
(224 reference statements)
1
64
0
Order By: Relevance
“…Our finding may, for example, help to relate the apparent similarities in the Fermi-surfaces of LNSCO 34 and LSCO 35 to the different superconducting properties of these compounds. In scanning tunnelling spectroscopy experiments, spatial modulations of the local density of states have been observed for different cuprate systems 37,38 . For 12-per cent doped LSCO spatial modulations on different length scales have been observed 39 ; for the interpretation of these, the existence of charge stripes may matter 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding may, for example, help to relate the apparent similarities in the Fermi-surfaces of LNSCO 34 and LSCO 35 to the different superconducting properties of these compounds. In scanning tunnelling spectroscopy experiments, spatial modulations of the local density of states have been observed for different cuprate systems 37,38 . For 12-per cent doped LSCO spatial modulations on different length scales have been observed 39 ; for the interpretation of these, the existence of charge stripes may matter 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Lateral confinement was achieved in a top-down approach and exploited in nano-electronic devices 10,11 . On the other hand, bottom-up microscopic electronic structure engineering based on intrinsic atomic scale lateral reconstructions, which are ubiquitous 18,19 in oxides, has received little attention.…”
Section: Main Textmentioning
confidence: 99%
“…Even though a number of reconstructions have been observed on the SrTiO 3 (001) surface [24][25][26], we focused on the so-called double-layer-TiO 2 (2×1) surfaces [27,28] because other more complex surfaces are not compatible with the (2×1) reconstruction under study here. It has been found that, on the double-layer-TiO 2 (2×1) surface, the role of O vacancy is the same as that in the missingrow structure described above.…”
Section: (A)mentioning
confidence: 99%